ACG Clinical Guideline: Disorders of the Hepatic and Mesenteric Circulation. (January 2020) - Simonetto, Douglas A.; Singal, Ashwani K.; Garcia-Tsao, Guadalupe; Caldwell, Stephen H.; Ahn, Joseph; Kamath, Patrick S.
Abstract : Disorders of the mesenteric, portal, and hepatic veins and mesenteric and hepatic arteries have important clinical consequences and may lead to acute liver failure, chronic liver disease, noncirrhotic portal hypertension, cirrhosis, and hepatocellular carcinoma. Although literature in the field of vascular liver disorders is scant, these disorders are common in clinical practice, and general practitioners, gastroenterologists, and hepatologists may benefit from expert guidance and recommendations for management of these conditions. These guidelines represent the official practice recommendations of the American College of Gastroenterology. Key concept statements based on author expert opinion and review of literature and specific recommendations based on PICO/GRADE analysis have been developed to aid in the management of vascular liver disorders. These recommendations and guidelines should be tailored to individual patients and circumstances in routine clinical practice.